(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2024)
Background: The present research includesa study length effect of quadrupole magnet on the properties of charged particles beam passing through it, the work included theoretical analysis using matrix expounding because it is optimum way to be the representative of beam along any optical system. Materials and Methods: we used a Matlab program to study the effect of effective length (Lmm) on the basic parameters of quadruple magnet lens. The values of effective length are from (500 mm to 1000 mm) , to determine focal length and the lens power. The results indicated that increasing the effective length led to a decrease in the horizontal and vertical focal length of the system, but for the power lens, the opposite behavior would be occurred. Results: The effective length (L) and the focusing factor (k), whose product gives us the reversed focal length of the magnetic lens, are the main parameters that govern the behavior of a charged particle beam passing a set of quadruple magnets. Any alteration in the value of any one of them so provides a new perspective. Conclusion: Two measures that are used to characterize lenses are the focal lengths and the lens power. Shorter focal lengths are associated with stronger lenses. The reciprocal of focal length is lens power. It characterizes different optical systems in terms of particle movement and the smallest possible focusing point.